Commuting Time and Sick-Day Absence of US Workers - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2018)
This paper analyzes the relationship between commuting time and sick-day absence of US workers. Using data from the Panel Study of Income Dynamics for the years 2011, 2013, and 2015, we find that a 1% increase in the daily commute of male workers is associated with an increase of around 0.018% in sick-day absences per year. In the case of women, the relationship is not significant. These results hold after controlling for individual fixed effects and socio-demographic characteristics, changes in jobs and places of residence, and differences in the self-reported health status of workers. By determining how commuting time is related to sickness absenteeism, we shed light on the relationship between commuting behavior and workers' health-related outcomes, measured by their labour supply.
Keywords: I10; J22; R2; R40; 330; commuting time; sickness absence; health-related outcomes; labour supply